2001
DOI: 10.1152/ajpheart.2001.281.3.h1066
|View full text |Cite
|
Sign up to set email alerts
|

Src tyrosine kinase is the trigger but not the mediator of ischemic preconditioning

Abstract: The signal cascade that triggers and mediates ischemic preconditioning (IPC) remains unclear. The present study investigated the role of the Src family of tyrosine kinases in IPC. Isolated and buffer-perfused rat hearts underwent IPC with three cycles of 5-min ischemia and 5-min reperfusion, followed by 30-min ischemia and 120-min reperfusion. The Src tyrosine kinase family-selective inhibitor PP1 was administered between 45 and 30 min before ischemia (early PP1 treatment) or for 15 min before IPC [early PP1-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 44 publications
5
39
0
1
Order By: Relevance
“…Indeed, Mockridge et al (24) found that PI3-kinase activation in a model of simulated ischemia-reperfusion in cardiomyocytes could be blocked by the Src kinase inhibitor PP2. PP2 also could block protection from IPC in rat heart (15). PP2 completely blocked Akt activation from ACh in the present study supporting a role for an Src kinase in this pathway.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, Mockridge et al (24) found that PI3-kinase activation in a model of simulated ischemia-reperfusion in cardiomyocytes could be blocked by the Src kinase inhibitor PP2. PP2 also could block protection from IPC in rat heart (15). PP2 completely blocked Akt activation from ACh in the present study supporting a role for an Src kinase in this pathway.…”
Section: Discussionsupporting
confidence: 81%
“…Markedly elevated levels of c-Src kinase activity were detected in human skin tumors (1). Myocardial ischemia-reperfusion caused an induction of c-Src protein expression (17); inhibition of c-Src with PPI reduces the extent of cellular injury.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of reperfusion, a 10% (wt/vol) solution of triphenyltetrazolium chloride in phosphate buffer was infused into the aortic cannula for 20 min at 37°C (16,17). The hearts were excised and stored at Ϫ70°C.…”
mentioning
confidence: 99%
“…We (176) have observed that degree of proteasome inhibition during reperfusion is dependent on length of ischemia and seems to correlate with levels of oxidized and ubiquitinated proteins and have suggested that the process known as dysregulation is occurring in which there is failure to degrade normal substrates of the proteasome. In support of this hypothesis, we (43) have recently shown that preservation of proteasome function with tocotrienol pretreatment decreases postischemic levels of phosphorylated c-SRC, which signals for ubiquitination and degradation by proteasome (93), and which is also known to be upregulated during ischemia and associated with poor outcomes (97). Further, we (51) have recently demonstrated that pretreatment of isolated hearts with the proteasome inhibitor lactacystin results in a greater accumulation of oxidized proteins and diminished degradation of oxidized actin in the postischemic heart, implying a mediatory role for proteasome.…”
Section: Proteasome Dysfunction In Myocardial Ischemiamentioning
confidence: 72%